Taxa de disparo e ativação de assembléias no hipocampo de ratos durante o processamento de uma memória aversiva - Lemos, Nelson Alessandretti de Mello (2012)
Hebb postulated that memory could be stored thanks to the synchronous activity of many neurons, building a neural assembly. Knowing of the importance of the hippocampal structure to the formation of new explicit memories, we used electrophysiological recording of multiple neurons to access the relevance of rate coding from neural firing rates in comparison to the temporal coding of neural assemblies activity in the consolidation of an aversive memory in rats. Animals were trained at the discriminative avoidance task using a modified elevated plus-maze. During experimental sessions, slow wave sleep periods (SWS) were recorded. Our results show an increase in the identified neural assemblies activity during post-training SWS, but not for the neural firing rate. In summary, we demonstrate that for this particular task, the relevant information needed for a proper memory consolidation lies within the temporal patters of synchronized neural activity, not in its firing rate